Epigenetic markers in the embryonal germ cell development and spermatogenesis - Odroniec, Amadeusz; Olszewska, Marta; Kurpisz, Maciej (Basic and clinical andrology, 2023)
Spermatogenesis is the process of generation of male reproductive cells from spermatogonial stem cells in the seminiferous epithelium of the testis. During spermatogenesis, key spermatogenic events such as stem cell self-renewal and commitment to meiosis, meiotic recombination, meiotic sex chromosome inactivation, followed by cellular and chromatin remodeling of elongating spermatids occur, leading to sperm cell production. All the mentioned events are at least partially controlled by the epigenetic modifications of DNA and histones. Additionally, during embryonal development in primordial germ cells, global epigenetic reprogramming of DNA occurs. In this review, we summarized the most important epigenetic modifications in the particular stages of germ cell development, in DNA and histone proteins, starting from primordial germ cells, during embryonal development, and ending with histone-to-protamine transition during spermiogenesis. La spermatogenèse est le processus de génération de cellules reproductrices mâles à partir de cellules souches spermatogoniales, dans l’épithélium séminifère du testicule. Au cours de la spermatogenèse, des événements spermatogéniques clés tels que l’auto-renouvellement des cellules souches et l’engagement dans la méiose, la recombinaison méiotique, l’inactivation méiotique du chromosome sexuel, suivis d’un remodelage cellulaire et chromatique des spermatides allongées se produisent, conduisant à la production de spermatozoïdes. Tous les événements mentionnés sont au moins partiellement contrôlés par les modifications épigénétiques de l’ADN et des histones. De plus, au cours du développement embryonnaire, une reprogrammation épigénétique globale de l’ADN se produit dans les cellules germinales primordiales. Dans cette revue, nous avons résumé les modifications épigénétiques les plus importantes dans les étapes particulières du développement des cellules germinales, dans l’ADN et les protéines histones, en partant des cellules germinales primordiales, au cours du développement embryonnaire, jusqu’à la transition histone-protamine pendant la spermiogenèse.